Method for preparing high-entropy alloy based on multi-physical field activation sintering
Patent Information
- Application Number
- CN202410594683.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-14
AI Technical Summary
[0004]本发明的目的在于针对现有技术中的上述不足,提供一种基于多物理场活化烧结制备高熵合金的方法,以解决现有的高熵合金制备存在成本高、周期长、加工复杂等的问题
[0027]本发明在烧结过程中采用低电压、大电流的交流电通过模具及粉末体系,粉末体系在电场、温度场、力场三场耦合下,通过焦耳热效应和电热聚焦的作用快速均匀升温,避免了传统烧结方法升温速率慢的问题。
Smart Images

Figure CN118543831B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-entropy alloy preparation, specifically relating to a method for preparing high-entropy alloys based on multi-physics field activation sintering. Background Technology
[0002] High-entropy alloys, as a new type of high-performance metallic material, have attracted widespread attention in the materials science field. Traditional alloy materials generally contain only one or two main elements, and their properties are optimized by adding a small amount of other components. In contrast, high-entropy alloys contain multiple elements (generally three or more), and possess excellent mechanical properties and functional characteristics.
[0003] Currently, common methods for preparing high-entropy alloys include mechanical alloying based on solid-state forming; liquid-phase forming methods such as laser cladding, induction melting, and directional solidification; and gas-phase forming methods such as magnetron sputtering and electron beam evaporation. These processes all have limitations in terms of equipment cost, difficulty in controlling parameters, inconvenient operation, forming time and quality, and environmental pollution, restricting the large-scale production and widespread application of high-entropy alloys. For example, the most commonly used vacuum melting method requires ensuring a good ingot microstructure, effectively removing gases and reducing non-metallic inclusions to improve alloy purity, and controlling temperature and cooling rate to minimize segregation and residual stress. While mechanical alloying greatly improves the corrosion resistance and uniformity of high-entropy alloy films, avoiding the high-temperature melting and solidification processes of ordinary metallurgical methods and achieving alloying at room temperature, it places relatively high demands on grinding equipment and the temperature and gas environment during the grinding process; otherwise, oxidation and defects may occur. Magnetron sputtering has simple equipment, is easy to control the coating thickness, and has good chemical composition. While high-entropy alloys exhibit uniform chemical composition, their application is limited to thin film preparation. Therefore, research should focus on the density and wear resistance of the coating. Electrochemical methods can directly obtain metals and alloys from solid oxides, reducing costs. However, graphite is commonly used as the anode in the electrolysis process, necessitating the prevention of carbon contamination and strengthening the corrosion resistance of alloy films. Laser additive manufacturing, as an emerging technology in recent years, can improve the performance of high-entropy alloys, ensure the uniformity of chemical composition, and improve microstructure. However, research on this technology is limited, requiring further refinement of laser additive manufacturing technology and equipment. Further in-depth research is needed on the relationship between its processes, microstructure, and performance. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned shortcomings in the prior art by providing a method for preparing high-entropy alloys based on multi-physics field activation sintering, thereby solving the problems of high cost, long cycle, and complex processing in existing high-entropy alloy preparation methods.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing high-entropy alloys based on multi-physics field activated sintering includes the following steps:
[0007] S1. Mix various elemental metal powders according to a predetermined atomic molar ratio to obtain a mixed powder;
[0008] S2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0009] S3. Dry the alloyed mixed powder and divide it into two groups. One group is treated with a pulsed magnetic field, and the other group is left untreated.
[0010] S4. The two sets of mixed powders are loaded into graphite molds respectively, and the electric field, temperature field and force field of the mixed powders are coupled using a thermal simulator to complete the pressing and sintering at the same time.
[0011] S5. After sintering, the pressure is unloaded, and the alloy sample is cooled to room temperature with the furnace to obtain a high-entropy alloy sample.
[0012] Furthermore, in step S1, the various elemental metal powders include Co, Cr, Fe, Ni, and Al, and are mixed according to the atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder.
[0013] Furthermore, in step S2, the grinding balls are made of Al2O3 or stainless steel, the diameter of the grinding balls is 8-10 mm, and the volume ratio of the grinding balls to the mixed powder is 2:3.
[0014] Furthermore, the planetary ball mill has a rotational speed of 110–160 pm and an effective milling time of 5–7 hours.
[0015] Further, in step S3, the mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C.
[0016] Furthermore, in step S3, the magnetic field strength of the pulsed magnetic field treatment is 1.5T, the pulse width is 10s, and the number of pulses is 30.
[0017] Furthermore, the graphite mold in step S4 includes a cylindrical body and an upper cover and a lower cover that cooperate with the cylindrical body; a cylindrical cavity is opened in the center of the cylindrical body, and the cavity contains mixed powder; both the upper cover and the lower cover are provided with cylindrical protrusions, and the cylindrical protrusions on the upper cover and the lower cover are respectively embedded in the upper opening and the lower opening of the cavity.
[0018] Further, the graphite mold was placed in the Gleeble-1500D thermal simulator, and the upper and lower covers at both ends of the graphite mold were connected to electrodes respectively.
[0019] Pressure and electric field are applied to both ends of the graphite mold. The mixed powder particles heat up rapidly due to the Joule heating effect. That is, during the heating stage of the mixed powder particles, the electric field, temperature field and force field of the mixed powder are coupled to complete the pressing and sintering at the same time.
[0020] Furthermore, the sintering parameters are as follows:
[0021] The sintering temperature is 800℃~1250℃;
[0022] The heating rate is 10℃ / s or 30℃ / s + furnace cooling;
[0023] The sintering pressure is 50 MPa;
[0024] The heat preservation time is 6 minutes.
[0025] Furthermore, the sintering temperature is 800℃, 950℃, 1100℃ or 1250℃.
[0026] The method for preparing high-entropy alloys based on multi-physics field activated sintering provided by this invention has the following beneficial effects:
[0027] In this invention, low-voltage, high-current alternating current is used to pass through the mold and powder system during the sintering process. Under the coupling of electric field, temperature field and force field, the powder system is rapidly and uniformly heated through the Joule heating effect and electrothermal focusing, thus avoiding the problem of slow heating rate in traditional sintering methods.
[0028] This invention employs multi-physics field coupling to activate and sinter high-entropy alloys, which is simple and low-cost; it can achieve near-net-shape forming, high material utilization, and high production efficiency, providing a fast, economical, and efficient new approach for the preparation of powder metallurgy high-entropy alloys, and is also applicable to other alloy systems.
[0029] This invention employs low-voltage, high-current alternating current through a mold and a powder system. The powder system rapidly and uniformly heats up under the coupled influence of an electric field, a temperature field, and a force field. Through the Joule heating effect and electrothermal focusing, CoCrFeNiAl is achieved. 0.5 Rapid densification of high-entropy alloys enables the rapid preparation of CoCrFeNiAl0.5 high-entropy alloys with no obvious voids, good surface oxidation, and good surface quality. Attached Figure Description
[0030] Figure 1 This is a flowchart of the method for preparing high-entropy alloys based on multi-physics field activation sintering according to the present invention.
[0031] Figure 2 Figure (a) is a schematic diagram of the graphite mold of the present invention, and Figure (b) is a schematic diagram of the graphite mold structure and a schematic diagram of the graphite mold coupling.
[0032] Figure 3 This is a metallographic schematic diagram of the cross-section of the alloy sample of the present invention.
[0033] Figure 4 This is a SEM image of the alloy sample of the present invention.
[0034] Figure 5 XRD pattern of the alloy sample of this invention Detailed Implementation
[0035] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.
[0036] Example 1
[0037] This embodiment provides a method for preparing high-entropy alloys based on multiphysics field activated sintering, referencing... Figure 1 Specifically, it includes the following steps:
[0038] Step S1: Mix various elemental metal powders according to a predetermined atomic molar ratio to obtain a mixed powder;
[0039] Step S2: Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0040] The grinding balls are made of Al2O3 or stainless steel, with a diameter of 8-10 mm. The volume ratio of grinding balls to mixed powder is 2:3. The planetary ball mill speed is 110-160 pm, and the effective grinding time is 5-7 h.
[0041] Since the raw materials of each element are elemental powders, the powder is alloyed after being mixed evenly using a ball mill. This alloying can be detected by energy dispersive spectroscopy using a scanning electron microscope. If the component content measured in the field of view is close to the nominal component, it is considered to be homogenized powder.
[0042] Step S3: Dry the alloyed mixed powder and divide it into two groups. One group is treated with a pulsed magnetic field, while the other group is left untreated.
[0043] The magnetic field strength for pulsed magnetic field treatment is 1.5T, the pulse width is 10s, and the number of pulses is 30.
[0044] The purpose of pulsed magnetic field treatment of powder in this embodiment is that ferromagnetic elements (Fe, Co, etc.) will make the powder composition more uniform under the action of magnetic field, which is beneficial to improving the molding quality of sintered samples.
[0045] The two sets of mixed powders were placed into quartz glass tubes and dried in a vacuum drying oven at 150°C.
[0046] Step S4: The two sets of mixed powders are respectively loaded into graphite molds, and the electric field, temperature field, and force field of the mixed powders are coupled using a thermal simulator. At the same time, the pressing and sintering are completed. Specifically, this includes the following:
[0047] refer to Figure 2 The graphite mold includes a cylindrical body and an upper cover and a lower cover that fit with the cylindrical body; a cylindrical cavity is opened in the center of the cylindrical body, and the cavity contains mixed powder; both the upper cover and the lower cover are provided with cylindrical protrusions, and the cylindrical protrusions on the upper cover and the lower cover are respectively embedded in the upper opening and the lower opening of the cavity.
[0048] Specifically, the graphite mold has a diameter of 30mm, a height of 40mm, and upper and lower covers with a thickness of 5mm and a center protrusion of 10mm (which are also used for pressing blanks). A cavity with a diameter of 8mm and a height of 10mm is reserved in the center for filling powder.
[0049] Place the graphite mold into the Gleeble-1500D thermal simulator and connect the upper and lower covers at both ends of the graphite mold to electrodes respectively.
[0050] Apply pressure to both ends of the graphite mold, i.e., apply a force field;
[0051] And conduct electricity through electrodes to apply an electric field;
[0052] The mixed powder particles heat up rapidly due to the Joule heating effect, i.e., a temperature field is applied.
[0053] That is, during the heating stage of the mixed powder particles, the electric field, temperature field and force field of the mixed powder are coupled to simultaneously complete the pressing and sintering.
[0054] The sintering parameters are:
[0055] The sintering temperature is 800℃~1250℃;
[0056] The heating rate is 10℃ / s or 30℃ / s + furnace cooling;
[0057] The sintering pressure is 50 MPa;
[0058] The heat preservation time is 6 minutes.
[0059] As a preferred embodiment, the sintering temperature is preferably 800℃, 950℃, 1100℃ or 1250℃.
[0060] Step S5: After sintering is completed, the pressure is unloaded, and the alloy sample is cooled to room temperature with the furnace to obtain a high-entropy alloy sample.
[0061] Example 2
[0062] This embodiment provides a method for preparing high-entropy alloys based on multi-physics field activated sintering, and CoCrFeNiAl 0.5 The preparation of high-entropy alloys is described, specifically including the following steps:
[0063] A1. Mix various elemental metal powders, including Co, Cr, Fe, Ni, and Al, according to an atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder.
[0064] A2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0065] The grinding balls are made of Al2O3 or stainless steel, with a diameter of 8-10 mm. The volume ratio of grinding balls to mixed powder is 2:3. The planetary ball mill rotates at 150 pm, and the effective grinding time is 6 hours.
[0066] A3. The mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C.
[0067] A4. The dried mixed powder is loaded into a graphite mold, and the pressing and sintering are completed simultaneously in a Gleeble-1500D thermal simulator with predetermined sintering parameters.
[0068] The sintering parameters are:
[0069] The sintering temperature is 800℃, the heating rate is 10℃ / s, the sintering pressure is 50MPa, and the holding time is 6min.
[0070] A5. After sintering, the pressure was gradually unloaded, and the alloy sample was cooled to room temperature with the furnace to obtain a CoCrFeNiAl alloy sample with dimensions of approximately φ8mm × 10mm. 0.5 High-entropy alloy sample UT-800.
[0071] Example 3
[0072] This embodiment provides a method for preparing high-entropy alloys based on multi-physics field activated sintering, and CoCrFeNiAl 0.5 The preparation of high-entropy alloys is described, specifically including the following steps:
[0073] B1. Mix various elemental metal powders, including Co, Cr, Fe, Ni, and Al, according to an atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder.
[0074] B2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0075] The grinding balls are made of Al2O3 or stainless steel, with a diameter of 8-10 mm. The volume ratio of grinding balls to mixed powder is 2:3. The planetary ball mill rotates at 150 pm, and the effective grinding time is 6 hours.
[0076] B3. The mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C.
[0077] B4. The dried mixed powder is loaded into a graphite mold, and the pressing and sintering are completed simultaneously in a Gleeble-1500D thermal simulator with predetermined sintering parameters.
[0078] The sintering parameters are:
[0079] The sintering temperature was 1100℃, the heating rate was 10℃ / s, the sintering pressure was 50MPa, and the holding time was 6min.
[0080] B5. After sintering, the pressure was gradually unloaded, and the alloy sample was cooled to room temperature with the furnace to obtain a CoCrFeNiAl alloy sample with dimensions of approximately φ8mm × 10mm. 0.5 High-entropy alloy sample UT-1100.
[0081] Example 4
[0082] This embodiment provides a method for preparing high-entropy alloys based on multi-physics field activated sintering, and CoCrFeNiAl 0.5 The preparation of high-entropy alloys is described, specifically including the following steps:
[0083] C1. Mix various elemental metal powders, including Co, Cr, Fe, Ni, and Al, according to an atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder;
[0084] C2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0085] The grinding balls are made of Al2O3 or stainless steel, with a diameter of 8-10 mm. The volume ratio of grinding balls to mixed powder is 2:3. The planetary ball mill rotates at 150 pm, and the effective grinding time is 6 hours.
[0086] C3. The mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C. The mixed powder is then subjected to pulsed magnetic field treatment.
[0087] The magnetic field parameters for pulsed magnetic field processing are:
[0088] The magnetic field strength is 1.5T, the pulse width is 10s, and the number of pulses is 30.
[0089] C4. The dried mixed powder is loaded into a graphite mold, and the pressing and sintering are completed simultaneously in a Gleeble-1500D thermal simulator with predetermined sintering parameters.
[0090] The sintering parameters are:
[0091] The sintering temperature was 1100℃, the heating rate was 10℃ / s, the sintering pressure was 50MPa, and the holding time was 6min.
[0092] C5. After sintering, the pressure was gradually unloaded, and the alloy sample was cooled to room temperature with the furnace to obtain a CoCrFeNiAl alloy sample with dimensions of approximately φ8mm×10mm. 0.5 High-entropy alloy sample PMT-1100.
[0093] Example 5
[0094] This embodiment provides a method for preparing high-entropy alloys based on multi-physics field activated sintering, and CoCrFeNiAl 0.5 The preparation of high-entropy alloys is described, specifically including the following steps:
[0095] D1. Mix various elemental metal powders, including Co, Cr, Fe, Ni, and Al, according to an atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder.
[0096] D2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill;
[0097] The grinding balls are made of Al2O3 or stainless steel, with a diameter of 8-10 mm. The volume ratio of grinding balls to mixed powder is 2:3. The planetary ball mill rotates at 150 pm, and the effective grinding time is 6 hours.
[0098] D3. The mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C. The mixed powder is then subjected to pulsed magnetic field treatment.
[0099] The magnetic field parameters for pulsed magnetic field processing are:
[0100] The magnetic field strength is 1.5T, the pulse width is 10s, and the number of pulses is 30.
[0101] D4. The dried mixed powder is loaded into a graphite mold, and the pressing and sintering are completed simultaneously in a Gleeble-1500D thermal simulator with predetermined sintering parameters.
[0102] The sintering parameters are:
[0103] The sintering temperature is 800℃, the heating rate is 10℃ / s, the sintering pressure is 50MPa, and the holding time is 6min.
[0104] D5. After sintering, the pressure was gradually unloaded, and the alloy sample was cooled to room temperature with the furnace to obtain a CoCrFeNiAl alloy sample with dimensions of approximately φ8mm×10mm. 0.5 High-entropy alloy sample PMT-800.
[0105] refer to Figure 3 , Figure 3 The image described is a scanning electron microscope (SEM) image of the cross-section of a sample after ball milling, with and without pretreatment of the metal powder using a pulsed magnetic field, followed by sintering at different temperatures using a Glebble-1500 instrument. Figure 3 (a) and (b) are CoCrFeNiAl without pulsed magnetic field treatment. 0.5 Microstructure of high-entropy alloy powder sintered at 800℃ and 1100℃, respectively; Figure 3 (c) and (d) are CoCrFeNiAl treated with pulsed magnetic field. 0.5 Microstructure images of high-entropy alloy powder sintered at 800℃ and 1100℃. It can be seen that, compared with the sample sintered without pulsed magnetic field treatment, the metal particles after pulsed magnetic field treatment are squeezed together, the contact area is increased, more particles change from non-contact to contact state, more sintering necks appear, and the densification process during sintering is accelerated.
[0106] refer to Figure 4 , Figure 4 (a) and (b) are CoCrFeNiAl without pulsed magnetic field treatment. 0.5 Surface scanning images of the microstructure of high-entropy alloy powder sintered at 800℃ and 1100℃, respectively. Figure 3 (c) and (d) are CoCrFeNiAl treated with pulsed magnetic field. 0.5 Microstructure scans of high-entropy alloy powder sintered at 800℃ and 1100℃ are shown. In comparison, the elemental composition of the sample treated with a pulsed magnetic field is more uniform, which is beneficial for improving the densification degree of the sample during sintering and thus enhancing its performance.
[0107] refer to Figure 5 , Figure 5The X-ray diffraction patterns of different sintered samples demonstrate that whether or not the powder is pretreated with a pulsed magnetic field, the crystal structure of the sample remains unchanged. Figure 5 All samples were composed of face-centered cubic (FCC) and body-centered cubic (BCC) structures.
[0108] Although specific embodiments of the invention have been described in detail with reference to the accompanying drawings, this should not be construed as limiting the scope of protection of this patent. Various modifications and variations that can be made by a person skilled in the art without inventive effort within the scope described in the claims still fall within the scope of protection of this patent.
Claims
1. A method for preparing high-entropy alloys based on multi-physics field activated sintering, characterized in that, Includes the following steps: S1. Mix various elemental metal powders according to a predetermined atomic molar ratio to obtain a mixed powder; S2. Add grinding balls to the mixed powder and complete the alloying in a planetary ball mill; S3. After drying the alloyed mixed powder, divide the mixed powder into two groups. One group is treated with a pulsed magnetic field, and the other group is not treated. The magnetic field strength of the pulsed magnetic field treatment in step S3 is 1.5T, the pulse width is 10s, and the number of pulses is 30. S4. The two sets of mixed powders are respectively loaded into graphite molds, and the electric field, temperature field and force field of the mixed powders are coupled using a thermal simulator, while the pressing and sintering are completed simultaneously; the graphite mold in step S4 includes a cylindrical body and an upper cover and a lower cover that fit with the body; a cylindrical cavity is opened in the center of the body, and the mixed powder is placed inside the cavity; both the upper cover and the lower cover are provided with cylindrical protrusions, which are respectively embedded in the upper opening and the lower opening of the cavity; Place the graphite mold into the Gleeble-1500D thermal simulator and connect the upper and lower covers at both ends of the graphite mold to the electrodes respectively. Pressure and electric field are applied to both ends of the graphite mold. The mixed powder particles heat up rapidly due to the Joule heating effect. That is, during the heating stage of the mixed powder particles, the electric field, temperature field and force field of the mixed powder are coupled to complete the pressing and sintering at the same time. The sintering parameters are: The sintering temperature is 800℃~1250℃; The heating rate is 10℃ / s or 30℃ / s + furnace cooling; The sintering pressure is 50 MPa; The heat preservation time is 6 minutes; S5. After sintering, the pressure is unloaded, and the alloy sample is cooled to room temperature with the furnace to obtain a high-entropy alloy sample.
2. The method for preparing high-entropy alloys based on multi-physics field activation sintering according to claim 1, characterized in that: In step S1, the various elemental metal powders include Co, Cr, Fe, Ni, and Al, and are mixed according to the atomic molar ratio of Co:Cr:Fe:Ni:Al of 1:1:1:1:0.5 to obtain a mixed powder.
3. The method for preparing high-entropy alloys based on multi-physics field activation sintering according to claim 1, characterized in that: In step S2, the grinding balls are made of Al2O3 or stainless steel, the diameter of the grinding balls is 8~10mm, and the volume ratio of the grinding balls to the mixed powder is 2:
3.
4. The method for preparing high-entropy alloys based on multi-physics field activation sintering according to claim 1, characterized in that: The planetary ball mill has a rotational speed of 110~160 pm and an effective milling time of 5~7 hours.
5. The method for preparing high-entropy alloys based on multi-physics field activation sintering according to claim 1, characterized in that: In step S3, the mixed powder is loaded into a quartz glass tube and dried in a vacuum drying oven at 150°C.
6. The method for preparing high-entropy alloys based on multi-physics field activated sintering according to claim 1, characterized in that, The sintering temperature is 800℃, 950℃, 1100℃ or 1250℃.
Citation Information
Patent Citations
Preparation method for high-entropy alloy
CN107130125A
Method for improving density and performance of ferromagnetic high-entropy alloy sintered through microwaves
CN111545746A